LEXICOLOGY AND LEXICOGRAPHY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article provides a comprehensive overview of lexicography and lexicology, two interconnected fields within linguistics thatfocus on the study and documentation of words. It distinguishes between practical lexicography, which involves the creation of dictionaries for everyday use, and theoretical lexicography, which explores the principles behind dictionary compilation.The article also delves into lexicology, examining key areas such as semantics, morphology, etymology, and phraseology, which collectively enhance our understanding of word meanings and relationships. By highlighting the interplay between these disciplines, the article emphasizes their collaborative role in advancing our knowledge of language dynamics and evolution. Overall, it serves as an informative resource for anyone interested in the intricacies of language and its representation through dictionaries